БЕЗТРАНСФОРМАТОРНЫЕ ПОВЫШАЮЩИЕ РЕГУЛЯТОРЫ ПЕРЕМЕННОГО НАПРЯЖЕНИЯ С СИНУСОИДАЛЬНЫМИ ВХОДНЫМ И ВЫХОДНЫМ ТОКАМИ - Зиновьев , Г.С.; Удовиченко, А.В. (Інститут електродинаміки НАН України, Київ, 2012)
The family of transistor transformerless regulatos of the alternating voltage possessing ability to raise output voltage, with the raised quality of formed output voltage and an input current are offered. Results of modelling of a basic regulator are presented and maintenance possibility' stable output voltage and possibility' of its regulation for the purposes of reactive power of a network or the purposes of the operated asynchronous electric drive is shown. The work is carried out under the State contract No. 13.G3631.0010 dated as of October 22, 2010. References 3, figures 4.